Analisis Dampak Lingkungan Pada Strategi Mitigasi Bencana Banjir Di Kelurahan Wonosari Kawasan Das Beringin Semarang - Syah Putra, Rizal Ichsan; Zulfa, Nely; Amarda, Pradangga Satriyaduta; Prisanty, Tiara Kristiani; Latifah, Anis (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Wonosari Village, located within the Beringin River Basin (DAS), Semarang City, is an area that regularly experiences flooding due to a combination of high rainfall, changes in upstream land use, and river sedimentation. Various mitigation strategies, both structural and non-structural, have been implemented by the government and the community. However, the implementation of these strategies has the potential to cause environmental impacts that require comprehensive analysis. This study aims to (1) identify existing flood mitigation strategies in Wonosari Village, (2) analyze the positive and negative environmental impacts of each strategy, and (3) formulate recommendations for more sustainable mitigation strategies. The research method used is a mixed-methods with a qualitative approach through in-depth interviews with stakeholders (BPBD, community leaders) and field observations, as well as a SWOT analysis to evaluate environmental impacts. The results of the study, which have been subjected to a SWOT analysis, indicate that structural strategies such as river normalization and embankment construction are effective in reducing short-term inundation, but have significant negative impacts in the form of loss of riparian vegetation, increased riverbank erosion, and changes in the aquatic ecosystem. On the other hand, non-structural strategies such as early warning systems and community education programs tend to have positive environmental impacts, but their effectiveness depends heavily on community participation and awareness. This study concludes that an integrated mitigation approach, which balances technical interventions with nature-based solutions and strengthening social capacity, is key to sustainably reducing flood risk in Wonosari Village.